2014
DOI: 10.1002/lt.23873
|View full text |Cite
|
Sign up to set email alerts
|

Role of cardiac catheterization and percutaneous coronary intervention in the preoperative assessment and management of patients before orthotopic liver transplantation

Abstract: Limited data regarding the optimal risk assessment strategy for evaluating candidates for orthotopic liver transplantation (OLT) exist. Our center has adopted a policy of performing cardiac catheterization (CATH) in patients with predefined risk factors, and this is followed by percutaneous coronary intervention (PCI) when it is indicated, even in the presence of negative stress test findings. The aim of this single-center, retrospective study of all patients who underwent OLT between 2000 and 2010 was to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 26 publications
1
60
1
1
Order By: Relevance
“…Our study is not without limitations. First, it is difficult to extrapolate our results to other populations with a different cardiovascular baseline risk, which is probably lower in our series than in those reported in North America and northern Europe . On the other hand, differences in etiology may contribute to a different prevalence of CAD.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Our study is not without limitations. First, it is difficult to extrapolate our results to other populations with a different cardiovascular baseline risk, which is probably lower in our series than in those reported in North America and northern Europe . On the other hand, differences in etiology may contribute to a different prevalence of CAD.…”
Section: Discussioncontrasting
confidence: 57%
“…As for therapy, our protocol stated that all stenosis >70% should be treated aggressively, whereas in 50%‐70% stenosis, the decision should be individualized. Although treatment of moderate stenosis is controversial, a recent study reported good outcomes when all patients with moderate stenosis were treated, regardless of stress test results …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of heart catheterization is that the presence of CAD can be immediately confirmed and treated with percutaneous coronary intervention. 119 This measure has reduced the perioperative mortality rate through reductions in the incidence of both fatal and nonfatal myocardial infarctions in LT. 119 Cardiopulmonary exercise testing is an important clinical tool to evaluate exercise capacity and exercise intolerance, and to predict the outcome of the patients. 120 Cardiopulmonary exercise testing is a sensitive and specific predictor for short-term survival of patients in the waiting list for LT 121 and after LT. 122 …”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Significant CAD is defined as a more than 50% decrease in the lumen diameter resulting in a hemodynamically significant reduction in coronary blood flow [43]. The increased use of coronary angiography and percutaneous coronary intervention before orthotopic liver transplant is also associated with significant reductions in postoperative coronary events and all-cause mortality [44]. In contrast, coronary interventions do not reduce mortality rates in orthotopic liver transplant patients with severe CAD [45].…”
Section: Preoperative Cardiac Evaluation Testsmentioning
confidence: 99%